Efficacy of levonorgestrel releasing intrauterine system in the treatment of symptomatic adenomyosis: comparison with dienogest - Sultana, Sharmin; Chowdhury, Priyanka; Renu, Rafikunnaher; Aziz, Itrat; Tarique, Mostafa M. Al; Sultana, Rebeka; Banu, Jesmine (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Adenomyosis is a common, estrogen-dependent, chronic gynecological condition that often presents with dysmenorrhea, menorrhagia, and an enlarged uterus. This study aimed to evaluate and compare the effectiveness of the levonorgestrel-releasing intrauterine system (LNG-IUS) and oral dienogest in the management of symptomatic adenomyosis. Methods: This randomized controlled trial was conducted in the department of reproductive endocrinology and infertility, Bangabandhu Sheikh Mujib medical university (BSMMU), Dhaka, Bangladesh, from April 2022 to March 2023. In this study, we included 32 women aged 25-45 years diagnosed with symptomatic adenomyosis (menorrhagia and dysmenorrhea) attending the outpatient department of reproductive endocrinology and infertility at BSMMU. Participants were assigned to two treatment groups: One group received LNG-IUS and other group received dienogest. Results: Baseline demographic and clinical characteristics were similar between the groups. The LNG-IUS group showed a significantly greater reduction in menstrual pain at both 3 months (VAS 1.7±2.9 vs. 4.1±2.8) and 6 months (VAS 0.9±2.5 vs. 3.9±3.0) compared to the dienogest group (p<0.05). Uterine volume decreased more in the LNG-IUS group over time, but the differences were not statistically significant. Regular menstrual flow was significantly more common in the LNG-IUS group at both follow-ups, while heavy bleeding persisted in a notable portion of the dienogest group (p=0.004 and p=0.002, respectively). Hemoglobin levels improved significantly more in the LNG-IUS group by 6 months (100% vs. 57.14%; p=0.017). Although adverse effects were more frequently reported in the dienogest group, the difference was not statistically significant. Conclusions: This study showed that LNG-IUS was more effective than oral dienogest in reducing pain, improving menstrual bleeding patterns, and increasing hemoglobin levels in women with symptomatic adenomyosis, with a lower incidence of side effects.